Do health professionals care about their health? A comparative study of doctors and people with non-medical university education - Nowicki, Marcin; Dokurno, Urszula; Cymerys, Maciej; Klimczak, Martyna; Andrzejewska, Magdalena (Polish Journal of Public Health, 2009)
Introduction. In general opinion doctors are considered to be paragons of proper health behaviour. The aim of our study was to assess if their lifestyles really fit to this image. Material and methods. The anonymous questionnaire distributed among group of 56 medicine doctors (42 females and 14 males) and control group of 62 people with non-medical university education (33 females and 29 males) was used to obtain data. Questionnaire consisted of 37 test and open questions considering alcohol and tobacco consumption, eating habits, sport activity and prophylactic examinations. The survey took place in January and February of 2008. Results. There was no significant statistical difference between the study and control group in: mean BMI values, awareness of own overweight, pattern and quality of meals, alcohol consumption and time spent weekly on sport activities and number of former and active tobacco smokers. More doctors declare to practice sport ‘regularly’ and “time to time’ than in the control group (Chi-squared test, p=0.032) and consume fruit and vegetables over 3 times a day (Chi-squared test, p=0.002). There are no differences both in awareness and practice of breast and cervix cancer prophylaxis between the groups of doctor and non-doctor women, also general poor participation in cervix and breast cancer prophylaxis was revealed. Conclusions. The survey proved that physicians’ lifestyle is not much healthier in comparison to people with nonmedical university education. The percentage of female doctors as well as women from the control group undergoing cytological examinations regularly and practicing breast self-examination is still too low. As doctors should be examples of proper health behaviours, teaching programs should put a higher emphasis on this problem among health professionals.